2021
DOI: 10.1002/cbin.11576
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐340‐5p increases telomere length by targeting telomere protein POT1 to improve Alzheimer's disease in mice

Abstract: Alzheimer′s disease (AD) is a chronic neurodegenerative disorder which is the primary cause of dementia in the elderly. Telomere attrition has been proposed as a hallmark of aging. Our study aimed to explore the mechanism of the protection of telomere 1 (POT1) in regulating telomere length and affecting cellular senescence in AD. The AD mouse model was established by d‐galactose and aluminum chloride, and the water maze test and dark avoidance test were used to detect the behaviors of mice and confirm the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Cognitive dysfunction is the main expression of AD. d -galactose- and aluminum chloride-induced dementia model, a reliable animal model that resembles human dementia, has been widely used to screen anti-AD agents. , Aluminum chloride could induce neuronal inflammation and Aβ deposition in mice, resulting in learning and memory impairment. , In this study, we used an AD animal model induced with d -galactose and aluminum chloride to explore the effects of GB on AD. Recent studies have indicated that GB could ameliorate the learning and memory ability of vascular dementia rats .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive dysfunction is the main expression of AD. d -galactose- and aluminum chloride-induced dementia model, a reliable animal model that resembles human dementia, has been widely used to screen anti-AD agents. , Aluminum chloride could induce neuronal inflammation and Aβ deposition in mice, resulting in learning and memory impairment. , In this study, we used an AD animal model induced with d -galactose and aluminum chloride to explore the effects of GB on AD. Recent studies have indicated that GB could ameliorate the learning and memory ability of vascular dementia rats .…”
Section: Discussionmentioning
confidence: 99%
“…The animals were randomized into three groups: Con group (control group), AD group (AD model group), and AD + GB group (GB-treated AD). The AD animal model was induced with d -galactose and aluminum chloride, according to previous studies. , Mice in the AD + GB group were intragastrically treated with 0.1% Ginkgolide B (Yuanye Biotechnology Co., Ltd. Shanghai, China) once daily for 2 weeks prior to the induction of AD, then intragastrically treated once daily for 2 weeks after the induction of AD. Mice in the AD and Con groups took the same amount of saline.…”
Section: Methodsmentioning
confidence: 99%
“…Several miRNAs have been described as regulators of the expression of factors that influence telomere dynamics [ 14 ]. We observed alterations in the expression of miRNAs previously described, such as regulators of the molecules involved in telomere homeostasis and oxidative stress response [ 46 , 47 , 48 ]. Specifically, we observed an increase in miR-155-5p in ICM patients, whose expression is associated with telomere and genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…The sham group mice received an intraperitoneal injection of PBS. AD model was established according to the previously described protocol 29,30 . In brief, mice were injected intraperitoneally with 150 mg/kg of d ‐galactose and were intragastrically administered 5 mg/kg of AlCl 3 once a day for 40 consecutive days.…”
Section: Methodsmentioning
confidence: 99%